Association of Interleukin 23 Receptor Polymorphisms with Anti-Topoisomerase-I Positivity and Pulmonary Hypertension in Systemic Sclerosis - AGARWAL, SANDEEP K. (2009)
OBJECTIVE: IL23R has been identified as a susceptibility gene for development of multiple autoimmune diseases. We investigated the possible association of IL23R with systemic sclerosis (SSc), an autoimmune disease that leads to the development of cutaneous and visceral fibrosis. METHODS: We tested 9 single-nucleotide polymorphisms (SNP) in IL23R for association with SSc in a cohort of 1402 SSc cases and 1038 controls. IL23R SNP tested were previously identified as SNP showing associations with inflammatory bowel disease. RESULTS: Case-control comparisons revealed no statistically significant differences between patients and healthy controls with any of the IL23R polymorphisms. Analyses of subsets of SSc patients showed that rs11209026 (Arg381Gln variant) was associated with anti-topoisomerase I antibody (ATA)-positive SSc (p = 0.001)) and rs11465804 SNP was associated with diffuse and ATA-positive SSc (p = 0.0001, p = 0.0026, respectively). These associations remained significant after accounting for multiple comparisons using the false discovery rate method. Wild-type genotype at both rs11209026 and rs11465804 showed significant protection against the presence of pulmonary hypertension (PHT). (p = 3×10(−5), p = 1×10(−5), respectively). CONCLUSION: Polymorphisms in IL23R are associated with susceptibility to ATA-positive SSc and protective against development of PHT in patients with SSc.